Design and performance of a small-scale acoustic wind tunnel at Wenzhou University for aerodynamic noise studies. (October 2022) - Niu, Xiaofei; Chen, Hongjun; Li, Yong; Jia, Xiangyang; Zhang, Yaowen; Yong, Xin; Li, Cheng
Highlights: The wind tunnel adopts an open-circuit, open-jet, and suction style. The wind tunnel is suitable for studying the self-noise of low-speed axial fans and airfoils. The turbulence intensity of the free jet in the potential core is measured between 0.15 and 0.22%. The noise levels of all test models at the frequencies of interest are far over the background noise. Abstract: A small-scale acoustic wind tunnel has been newly built at Wenzhou University to study the aerodynamic noise generation and suppression for various bodies immersed in a fluid flow, especially for the airfoil and low-speed axial fans. The design principle, the overall layout, and key components of the wind tunnel are presented in this paper. This open-circuit and suction-type wind tunnel has an open-jet test section of 0.5 m × 0.4 m and can achieve a maximum wind speed of 60 m/s, corresponding to the Reynolds number of 1.8 × 10 6 based on the hydraulic diameter of the tunnel. The acoustic characteristics of the wind tunnel have shown a satisfactory result of low background noise levels comparable to other university wind tunnels worldwide. The turbulence intensity of the free jet in the potential core is measured between 0.15 and 0.22 %. Aeroacoustic measurements have been finally performed on a few benchmark models, including a rectangular cavity, a flat plate with blunt/sharp trailing edges, a tandem rod-airfoil, and a circular rod. The noise levels of all test models at the frequencies of interest are far in excess of the free-jet background noise, making the wind tunnel well suitable for aerodynamic noise studies.